THE CONSTRUCTION OF SPIRITUAL-WELLBEING IN THE COMMUNITY OF TARIQAH - Chabib Musthofa (JICSA : Journal of Islamic Civilization in Southeast Asian, 2014)
This paper discusses the construction of spiritual wellbeing in the community of tariqah. Myths, philosophy, and science, have all contributes in proposing descriptions pertaining to the mystery of human beings. Welfare, happiness, and prosperity, are of essential themes within the main subject in the study of social sciences, particularly in the discipline of Social Work. These themes became a research trend in a number of Social Work studies towards the end of the twentieth century. The orientation or purpose of religion on its adherents is manifested by providing information and rules relating to how to behave well to themselves, to God, to other human beings, and to their environment. This regulation is more accurately described as a practical living mechanism loaded with commands, prohibitions, and suggestions that lead to establishment of legal categories for each activity in a given context.